Patient-centered Information Systems - Brennan, P. Flatley; Kuang, Y.-S.; Volrathongchai, K. (Yearbook of Medical Informatics, 2000)
Patient-centered information systems augment traditional approaches to health information management with specific functions designed to support patient participation in health care decision making and treatment activities. In addition to computer-based record systems and business management applications, patient-centered information systems must include functionality that support communication between clinician and patient, and that provide information and peer support in a timely fashion to the patient. Current progress in information systems demonstrates the existence and feasibility of consumer health informatics, patient access to computerized clinical records, and technical and organizational solutions to integrating computerized patient information systems. We are now proposing a model of patient -centered system that incorporates all those components, and provides a vision of the future.